More than just a CRIS - How CRIStin is building a national infrastructure for Open Access - Karlstrøm, Nina (My University, 2016)
Keynote presentation at RepoFringe 2016 under the theme of 'The Nuts and Bolts of Open' by Nina Karlstrøm of CRIStin (Current Research Information SysTem In Norway).
Keywords: Open Access